Carta de Roberto H. Todd a Enrique González Mena - Todd, Roberto H.; González Mena, Enrique (My University, 1940)
Solicitud de información para artículos sobre el establecimiento de la coalición.
Keywords: Partido Republicano (Puerto Rico); Partido Socialista Puertorriqueño.; Barceló, Antonio R., 1868-1938; Tous Soto, José, 1874-1933; Towner, Horace Mann, 1855-1932; Weeks, John W.